2020
DOI: 10.3390/cancers12061640
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Brain Metastases in the Era of Target Therapies: An Overview

Abstract: Malignant melanoma is the third most common type of tumor that causes brain metastases. Patients with cerebral involvement have a dismal prognosis and their treatment is an unmet medical need. Brain involvement is a multistep process involving several signaling pathways such as Janus kinase/signal Transducer and Activator of Transcription (JAK/STAT), Phosphoinositide 3-kinase/Protein Kinase B (PI3K/AKT), Vascular Endothelial Growth Factor and Phosphatase and Tensin Homolog (PTEN). Recently therapy that targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 133 publications
(148 reference statements)
0
23
0
Order By: Relevance
“…The role of this novel therapy in patients with brain metastases was long unexplored since many studies excluded patients with intracranial metastasis. Finally, studies that included these patients showed an intracranial disease control rate of 60–79% and a median overall survival of 9.5 and 11.2 months, proving that targeted therapy has an effect despite the blood brain barrier [ 65 ]. However, all this data is accurate for BRAFV600E mutated tumors, but not for melanoma with an NRAS mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of this novel therapy in patients with brain metastases was long unexplored since many studies excluded patients with intracranial metastasis. Finally, studies that included these patients showed an intracranial disease control rate of 60–79% and a median overall survival of 9.5 and 11.2 months, proving that targeted therapy has an effect despite the blood brain barrier [ 65 ]. However, all this data is accurate for BRAFV600E mutated tumors, but not for melanoma with an NRAS mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicates that glioma tumors with low TMB are more likely to respond to IT (19). Clinical trials have demonstrated that IT can work for intracranial metastatic disease (20,21). Clinically significant tumor mutations are also annotated within the tumor biobank data repository.…”
Section: Methodsmentioning
confidence: 99%
“…Among melanoma patients with CNS metastases, those with LMD have the worst outcomes, with overall survival from diagnosis of typically weeks to a few months (1,2). Patients with parenchymal brain metastases have multiple treatment options including surgery, stereotactic radiosurgery, systemic therapies including the BRAF and MEK inhibitors, monotherapy with the immune checkpoint inhibitors ipilimumab or pembrolizumab, and/or the combination ipilimumab and nivolumab, which have demonstrated efficacy in clinical trials for metastatic melanoma patients with parenchymal brain metastases (3)(4)(5)(6)(7)(8). In contrast, there are very few treatment options for LMD patients (9,10), especially once patients develop LMD while on these agents.…”
Section: Introductionmentioning
confidence: 99%